The Evolution of Micromechanical Properties for Zr-Based Metallic Glass Induced by Laser Shock Peening - Li, Yansen; Wang, Zhitao; Wei, Yanpeng; Chen, Tianyu; Zhang, Chunfeng; Huan, Yong; Zhang, Kun; Wei, Bingchen (Frontiers in Materials, 2021)
The micromechanical properties of Zr-based metallic glass (MG) induced by laser shock peening (LSP) were studied through the use of nanoindentation. The serrations in representative load-displacement (P-h) curves exhibited a transformation from stairstep-like to ripple-shaped from untreated zone to shock region, which implied an increase in plastic deformation ability of material after LSP. Significant hardening was also observed in the impact zone, which can be attributed to the effect of compressive residual stress. Both increase in hardness and plastic deformation ability in shock region indicate the excellent effect of LSP on the micromechanical properties of investigated Zr-based MG, which provide a new way to study the deformation mechanism in metallic glasses and a further understanding of plasticization.